Repeat screening for syphilis in pregnancy as an alternative screening strategy in the UK: a cost-effectiveness analysis. Issue 11 (19th November 2020) - Huntington, Susie; Weston, Georgie; Seedat, Farah; Marshall, John; Bailey, Heather; Tebruegge, Marc; Ahmed, Imtyaz; Turner, Katy; Adams, Elisabeth
Abstract : Objectives: To assess the cost-effectiveness of universal repeat screening for syphilis in late pregnancy, compared with the current strategy of single screening in early pregnancy with repeat screening offered only to high-risk women. Design: A decision tree model was developed to assess the incremental costs and health benefits of the two screening strategies. The base case analysis considered short-term costs during the pregnancy and the initial weeks after delivery. Deterministic and probabilistic sensitivity analyses and scenario analyses were conducted to assess the robustness of the results. Setting: UK antenatal screening programme. Population: Hypothetical cohort of pregnant women who access antenatal care and receive a syphilis screen in 1 year. Primary and secondary outcome measures: The primary outcome was the cost to avoid one case of congenital syphilis (CS). Secondary outcomes were the cost to avoid one case of intrauterine fetal demise (IUFD) or neonatal death and the number of women needing to be screened/treated to avoid one case of CS, IUFD or neonatal death. The cost per quality-adjusted life year gained was assessed in scenario analyses. Results: Base case results indicated that for pregnant women in the UK (n=725 891), the repeat screening strategy would result in 5.5 fewer cases of CS (from 8.8 to 3.3), 0.1 fewer cases of neonatal death and 0.3 fewer cases of IUFD annually compared with the single screening strategy. This equates to an additional £1.8 million per case of CS prevented. When lifetime horizon was considered, the incremental cost-effectiveness ratio for the repeat screening strategy was £120 494. Conclusions: Universal repeat screening for syphilis in pregnancy is unlikely to be cost-effective in the current UK setting where syphilis prevalence is low. Repeat screening may be cost-effective in countries with a higher syphilis incidence in pregnancy, particularly if the cost per screen is low.